Phytotherapeutic practices of a folk medicinal practitioner in Dinajpur district, Bangladesh - Rifat Shah, Maidul Islam, Fazlay Rabbi, Nasrin Akter Shova, Aysha Akter, Hasna Akter, Istieake Ahmed, Erena Islam, Mohammed Rahmatullah (Journal of Applied Pharmaceutical Science, 2017)
The phytotherapeutic practices of a folk medicinal practitioner (FMP), practicing in Kaliaganj village of Dinajpur district, Bangladesh, was documented. Interviews of the FMP were carried out with the help of a semi-structured questionnaire and guided field-walk method. The FMP was observed to use a total of 48 plants distributed into 36 families for treatment of diverse diseases, which included respiratory tract disorders, gastrointestinal disorders, skin disorders, leucorrhea, urinary disorders, menstrual disorders, physical weakness, edema, Parkinson’s disease (body tremors), piles, bleeding through anus or penis, stone in urinary tract, and bone fracture. Most of the formulations used to treat diseases consisted of more than one plant species. Taken together, most of the formulations appeared to be quite different from plant formulations used by other FMPs in Dinajpur district as well as other places of Bangladesh (as observed in our previous field observations) and as such merit further research towards discovery of new drugs.
Keywords: Ethnomedicine, Kaliaganj, Dinajpur, Bangladesh.